Inflation Dynamics and Macroeconomic Determinants in BRICS-T Economies: Panel Causality Analysis (Third Sector Social Economic Review, 2025)
This study analyzes inflation dynamics and their relationship with key macroeconomic determinants in the BRICS-T economies (Brazil, Russia, India, China, South Africa, and Türkiye using econometric methods. Examining inflation within the framework of various theoretical approaches, the study investigates the effects of policy tools such as money supply, budget deficit, interest rate, exchange rate, and balance of payments on inflation. The findings reveal that these variables exert significant impacts on inflation and exhibit heterogeneous structures across countries; long-run relationships indicate that budget deficit, M3 money supply, and exchange rate have positive effects on inflation, while the real interest rate has a negative effect, and the relationship between the balance of payments and inflation displays a more complex dynamic. Analyses conducted using the Emirmahmutoğlu and Köse (2011) panel causality test reveal the presence of diverse causal relationships among countries. Specifically, it is found that inflation in some countries demonstrates strong relationships with real interest rates, exchange rates, and budget deficits, but no reciprocal causal relationship exists between money supply and inflation. These results underscore that inflation in BRICS-T countries cannot be reduced to a single factor, emphasizing the necessity for policymakers to develop more comprehensive strategies for combating inflation, taking into account country-specific differences. The study aims to contribute to the effectiveness of inflation-fighting policies in these nations.